An Evaluation on the Flexural Strength of Heat Cure Polymethyl methacrylate Denture Base Resin with and without Reinforcement of Polyethylene Fiber - Pathak, Binita; Mathema, S.; Sharma, R. (Journal of Nepalese Prosthodontic Society, 2018)
Introduction: Polymethyl methacrylate as denture base material is not ideal in many aspects. The primary problem is its poor strength characteristics, including low impact and flexural strength. The fatigue failure occurs when the denture base deforms repeatedly through occlusal forces, hence dentures tend to break during usage in due course of time. The aim of this study was to measure and compare the flexural strength of heat cure Polymethyl methacrylate denture base resin with and without reinforcement of polyethylene fiber.Method: A total of 52 specimens (maxillary complete denture) were divided into 2 groups (n=26); Group A(Control): Dentures without reinforcement, Group B: Dentures reinforced with Polyethylene fiber. All specimens were subjected to three-point bending test in UTM. A flexural load was applied to each maxillary complete denture at a speed of 5mm/min until fracture and the flexural load required to break specimen was recorded.Results: The mean values and standard deviation of each test specimen group was calculated and statistical analysis of obtained values was done using ANOVA. Mean flexural strength for Group A was 142.66±29.95 MPa and Group B was 218.88±29.96 MPa. Group comparison showed a statistically significant difference (p